Trademark Protection or Silencing Women? Feminist Jurisprudence on Article 20 of TRIPS, DS467 WTO, and Plain Tobacco Packaging - ZAB, Zian Ibnu (International Journal Labs, 2025)
The WTO DS467 dispute over tobacco plain packaging policy questions whether the right to brand cigarettes is more important than public health. This research uses an interdisciplinary normative legal approach to analyze the Panel and Appellate Body reports of DS467 through critical deconstruction. Drawing on the methods of domination (MacKinnon), asking the marginalized question (Bartlett), and the concept of juridical silencing (Finley), as well as a dogmatic-conceptual study of Article 20 TRIPS and the Ethics of Care, this research finds that the interpretation of Article 20 TRIPS is driven by commercial interests that place brand rights in a privileged position, while communal suffering and health—especially the burden of care borne by many women—are reduced to technical data. The findings reveal that WTO legal reasoning systematically marginalizes humanitarian perspectives by prioritizing abstract market logic over the lived experiences of caregivers and health workers. This research offers a prescriptive rereading of Article 20 TRIPS, in which the right to health and state sovereignty should be the normative priority, so that restrictions on the use of brands to protect public health can be justified, with the burden of proof shifted to the brand owner. The implications of this study extend beyond the DS467 case, suggesting that feminist jurisprudence can provide a transformative framework for reinterpreting international trade law to better align with human rights principles and dignity. This reading aims to shift the international trade regime from the dominance of market logic to the upholding of communal well-being and human dignity.